2020
DOI: 10.3390/f11070746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental Impact on Selected Properties of Lime (Tilia Cordata Mill.) Wood

Abstract: The external and internal factors in the tree development process affect wooden structures and properties. They depend on, for example, a plant species, its age, part and growth conditions. The present study investigated the chemical structure and physical properties of the common urban tree species: small-leaved lime (Tilia cordata Mill.). The properties of trees growing in an urban agglomeration, by a roadside and in a forest, i.e., areas varying in degrees of an environmental stress impact, were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The overall chemical composition of bark, including main components such as lignin, cellulose, holocellulose, and extractives, is summarized in Table 2. The sum of main constituents exceeded 100% because the presented values were calculated in relation to the wood dry matter due from the imperfection of wet methods, which are commonly used to determine the compositions of lignocellulosic materials [38]. The acidity of oak bark is beneficial, since a pH value of about 4-5 is required to obtain an optimal pressing time for amino resins [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall chemical composition of bark, including main components such as lignin, cellulose, holocellulose, and extractives, is summarized in Table 2. The sum of main constituents exceeded 100% because the presented values were calculated in relation to the wood dry matter due from the imperfection of wet methods, which are commonly used to determine the compositions of lignocellulosic materials [38]. The acidity of oak bark is beneficial, since a pH value of about 4-5 is required to obtain an optimal pressing time for amino resins [2].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1. Method of sample preparation for shear strength testing according to EN 314-1[38] (b 1 -25 ± 0.5 mm; b 2 -2.5 ± 0.5 mm; l 1 -25 ± 0.5 mm; l 2 -minimum distance between the grips of the testing machine-50 mm).…”
mentioning
confidence: 99%
“…In order to further characterize the material, the content of the extractives, ash, carbohydrates, and lignin was determined on the accepted material of the three tree genera samples collected in summer and winter separately ( Table 2 ), as the asserted anatomical differences between conventional wood and tree pruning wood also influence the chemical composition of the material, which can be important to know how to facilitate an optimal utilization. In comparison with pure wood samples of oak ( Ghavidel et al, 2020 ), linden ( Kusiak et al, 2020 ), and maple ( Výbohová et al, 2018 ), the content of carbohydrates found in the pruning residue is lower, while the amount of extractives and ash is higher. The main reason for this circumstance is most likely the high content of bark found in the samples, which features a low amount of carbohydrates and a high amount of extractives and ash ( Hakkila, 1989 ).…”
Section: Resultsmentioning
confidence: 98%
“…The main reason for this circumstance is most likely the high content of bark found in the samples, which features a low amount of carbohydrates and a high amount of extractives and ash ( Hakkila, 1989 ). Furthermore, it has been reported that high environmental stress, such as found in urban street environments, can lead to an increase in extractive components ( Gershenzon, 1984 ) and a reduction in cellulose and lignin in the xylem ( Kusiak et al, 2020 ). No meaningful differences in chemical composition between samples collected in summer and winter could be discerned.…”
Section: Resultsmentioning
confidence: 99%
“…These animals were subjected to three diets with different lignocellulosic compositions ( Figure 1 ): Diet 1 (D1), enriched in cellulose and hemicellulose, was composed of linden leaf and carrots (corresponding to the standard diet provided to pill-bugs bred in our laboratory)—Diet 2 (D2), enriched in lignin, was composed of poplar wood and Diet 3 (D3), enriched in cellulose, was composed of cellulosic paper (Whatman™ 3MM CHR Cellulose). The relative proportions of lignocellulose in the components of these diets were as follows: Linden leaf (40% cellulose, 20% hemicellulose and 20% lignin; [ 30 ]), carrots (10% cellulose, 6% hemicellulose and 3% lignin; [ 31 ]), Poplar (23% cellulose, 52% hemicellulose and 16% lignin; [ 32 ]), cellulosic paper (98% cellulose, Whatman TM ). All diets were previously sterilized in Stericlin ® self-seal pouches (each pouch containing one ration) using high-pressure steam.…”
Section: Methodsmentioning
confidence: 99%